Madureso Tradition Becomes a Marriage Taboo for Prospective Brides in Sucen Area, Bayan Sub-District, Purworejo City - Nurmala Sari, Titik (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This research is motivated by the culture of the community that still holds customs and is considered a hereditary tradition, they must preserve it should not be abandoned let alone removed. Although socially the current society is very modern, but in certain areas still find traditions that are held firmly by the community regarding the prohibition of madureso marriage which is still carried out until now. Madureso marriage is a prohibition of marriage where parents or elders do not allow their children to marry someone who has the same direction of the house facing mojok wetan or northeast of such a marriage prohibition. This research is a field rieserch and to collect information through interviews with the community and make observations to the place in order to know the implementation directly. The research uses descriptive-analytical analysis techniques. The conclusion is that the prohibition or restriction of marriage has actually been believed or has been followed by the residents of Sucen Purworejo from generation to generation from ancestors. Therefore, the residents of sucen Purworejo believe and do not marry if the bride and groom have a house facing each other. Because they believe that if they violate it, there will be a disaster in the marriage they do.